(Critical Review) Repositioning Science and Technology Education for Security and National Economic Growth and Development in Nigeria - Ibrahim Mohammed Isa (International Journal of Asian Education, 2022)
This article examined the repositioning of science and technology education for security and economic growth and development in Nigeria. The wreck on the nation's image by the incidences of insurgency has caused negative effects on the nation's security and economic development. Security issues are presently major challenges in Nigeria, especially in Northern Nigeria. Furthermore, the continuous rise in insecurity and deterioration in the economic development in Nigeria has called for concern among researchers and policymakers over the years. This article highlights the need for rebranding Nigerians through the internal process of repositioning the science and technology education system for national security and economic sustainability. Literature and other research papers using to gather information. The paper recommends that the nation adopt a proactive approach to improving the teaching and learning of science and technology education professionally and empowering youth while taking everlasting measures to curtail the issues of insurgencies in Nigeria. In other words, we need to reposition our youth's mental reasoning and economically empower them to certify the demands of the modern world. Repositioning Nigerian is one of the fruitful tools to achieve this objective, and rebranding directs the power and energy of Nigerians toward academic and productive goals